Peran Misi Kontekstual Dalam Menghadapi Multi Krisis Global - Sembiring, Tabita Br (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2025)
The ongoing global multidimensional crisis is greatly affecting people's lives in all parts of the world, including in Indonesia. Be it the poverty crisis, social disintegration and also the environment. The global multidimensional crisis presents complex problems to society, in this case the church must also carry out God's mission as a responsibility to be believers in God, because God sent the church to carry out His mission to all people in the world with all the problems they are experiencing. Carrying out God's mission to a pluralistic society with diverse cultures and problems also requires a way to answer these needs, namely carrying out the mission holistically. The aim is to carry out God's mission which pays attention to human life holistically. Through this mission, it is hoped that they can believe in the true God in the situations and conditions they are facing.